Enhancing Corporate Performance Through Good Corporate Governance: Evidence from Kalla Group - Idris, Hariany; Sangkala, Masnawaty; Syachbrani, Warka (Technium Social Sciences Journal, 2025)
This study investigates the relationship between Good Corporate Governance (GCG) practices and corporate performance within Kalla Group, one of the largest conglomerates in Eastern Indonesia. GCG was evaluated through five core dimensions: transparency, accountability, responsibility, independence, and fairness. Firm performance was assessed using both financial indicators—Return on Assets (ROA) and Return on Equity (ROE)—and non-financial measures such as employee satisfaction and innovation. A quantitative research design was employed, applying multiple linear regression analysis to data collected from 39 employees across three subsidiaries of Kalla Group. Primary data were obtained through questionnaires, while secondary data were derived from annual and financial reports. The empirical findings indicate that all GCG variables significantly and positively affect firm performance. Transparency demonstrates the strongest influence (β = 0.526), followed by responsibility (β = 0.619), accountability (β = 0.358), independence (β = 0.282), and fairness (β = 0.285). The coefficient of determination (R² = 0.863) suggests that 86.3% of performance variations can be explained by governance practices, with the remaining 13.7% influenced by external factors. These results highlight the strategic importance of effective GCG implementation in enhancing corporate performance, building stakeholder trust, and sustaining long-term competitiveness. The study contributes empirical evidence to the governance–performance nexus in emerging market contexts.